Membangun Kesadaran Digital: Sosialisasi Hak dan Kewajiban dalam Penggunaan Media Sosial di SMA 1 Yapis Merauke - Dyana Hesti Kamila; Roro Anggi Sukmawati; Syadila Ainun Nisa; Yulidiana Zesa Azis; Poetri Enindah Suradinata; Zegovia Parera; Nasri Wijaya; Ahmad Ali Muddin; Anton Johanis Silubun (Sagu: Jurnal Pengabdian Masyarakat, 2025)
In the era of globalization, social media has become the main communication tool that affects people's lives, especially teenagers. The community service activity entitled "Wise at the Fingertips: The Importance of Understanding Rights and Obligations in Using Social Media" was implemented at SMA 1 Yapis Merauke to improve digital legal literacy among students. Through interactive lecture methods, group discussions, and case study simulations, this activity aims to provide an understanding of the ITE Law and legal issues related to the use of social media. Although attended by only 9 students, this activity succeeded in creating an atmosphere of in-depth discussion and increasing students' awareness of the legal risks that may arise from their online activities. Evaluation results showed a significant increase in understanding of digital ethics and social media responsibility. This activity emphasizes the importance of communicative and relevant legal education to form a wise and responsible young generation in using social media. Recommendations for the development of similar programs include expanding the range of participants and collaborating with more schools.